Picalm, a novel regulator of GLUT4-trafficking in adipose tissue - Jasmin Gaugel; Neele Haacke; Ratika Sehgal; Markus Jähnert; Wenke Jonas; Anne Hoffmann; Matthias Blüher; Adhideb Ghosh; Falko Noé; Christian Wolfrum; Joycelyn Tan; Annette Schürmann; et al. (Elsevier, 2024)
Objective: Picalm (phosphatidylinositol-binding clathrin assembly protein), a ubiquitously expressed clathrin-adapter protein, is a well-known susceptibility gene for Alzheimer's disease, but its role in white adipose tissue (WAT) function has not yet been studied. Transcriptome analysis revealed differential expression of Picalm in WAT of diabetes-prone and diabetes-resistant mice, hence we aimed to investigate the potential link between Picalm expression and glucose homeostasis, obesity-related metabolic phenotypes, and its specific role in insulin-regulated GLUT4 trafficking in adipocytes. Methods: Picalm expression and epigenetic regulation by microRNAs (miRNAs) and DNA methylation were analyzed in WAT of diabetes-resistant (DR) and diabetes-prone (DP) female New Zealand Obese (NZO) mice and in male NZO after time-restricted feeding (TRF) and alternate-day fasting (ADF). PICALM expression in human WAT was evaluated in a cross-sectional cohort and assessed before and after weight loss induced by bariatric surgery. siRNA-mediated knockdown of Picalm in 3T3-L1-cells was performed to elucidate functional outcomes on GLUT4-translocation as well as insulin signaling and adipogenesis. Results: Picalm expression in WAT was significantly lower in DR compared to DP female mice, as well as in insulin-sensitive vs. resistant NZO males, and was also reduced in NZO males following TRF and ADF. Four miRNAs (let-7c, miR-30c, miR-335, miR-344) were identified as potential mediators of diabetes susceptibility-related differences in Picalm expression, while 11 miRNAs (including miR-23a, miR-29b, and miR-101a) were implicated in TRF and ADF effects. Human PICALM expression in adipose tissue was lower in individuals without obesity vs. with obesity and associated with weight-loss outcomes post-bariatric surgery. siRNA-mediated knockdown of Picalm in mature 3T3-L1-adipocytes resulted in amplified insulin-stimulated translocation of the endogenous glucose transporter GLUT4 to the plasma membrane and increased phosphorylation of Akt and Tbc1d4. Moreover, depleting Picalm before and during 3T3-L1 differentiation significantly suppressed adipogenesis, suggesting that Picalm may have distinct roles in the biology of pre- and mature adipocytes. Conclusions: Picalm is a novel regulator of GLUT4-translocation in WAT, with its expression modulated by both genetic predisposition to diabetes and dietary interventions. These findings suggest a potential role for Picalm in improving glucose homeostasis and highlight its relevance as a therapeutic target for metabolic disorders.